Performance of seismic shear panels under near-field motions - Mariella Diaferio, Mariella (International Journal of Engineering and Technology, 2018)
The purpose of this study is to describe the structural response of steel frames with different stiffness and geometrical characteristics subjected to near-field earthquakes. Such actions, in fact, may be responsible of high levels of damage, as they are characterized by pulses of high amplitude. Thus, the effects on the structures are quite different from the ones induced by far-field earthquakes. In detail, the main aim is to evaluate the performance of such frames equipped with passive devices: two hysteretic dampers are considered which during the seismic action are mainly interested by shear stresses.  Nevertheless, the main characteristics of their hysteretic behavior are different and, consequently, for a correct use the comparison of the performance is an important tool. Thus, the response of the protected frames is evaluated varying the characteristics of the near-field motions.